POTENSI SANTRI DALAM TRANSFORMASI DIGITAL LITERACY MEMASUKI ERA REVOLUSI INDUSTRI 4.0 DI PONDOK PESANTREN MODERN - Tulaihah Ning Safitri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2020)
This study aims to see the potential of students in digital literacy transformation entering the era of the industrial revolution 4.0 at the Modern Muhammadiyah Boarding School Sleman Islamic Boarding School, Yogyakarta. This study used descriptive qualitative method. Data were collected through observation and interviews with 10 students. The results of this study found that students have mastered the technology of digital literacy transformation of students in the potential of mastering digital literacy. This is because Islamic boarding schools still limit the length of time they use technology. Although this pesantren has used modern pesantren. Pesantren leaders must balance religious education with technology so that graduates are not less competitive when they enter tertiary institutions and the world of work. For future researchers, it will be deeper in digging up information and using more samples.